2015
DOI: 10.1111/hepr.12500
|View full text |Cite
|
Sign up to set email alerts
|

miR‐486 regulates metastasis and chemosensitivity in hepatocellular carcinoma by targeting CLDN10 and CITRON

Abstract: Our data indicated that miR-486 may function as a novel tumor suppressor in HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 28 publications
1
42
0
Order By: Relevance
“…However, treatment outcomes are poor due to unfavorable pharmacokinetics, low tumor accumulation and high rates of sorafenib resistance in HCC patients (5). Evidence has shown that, some miRNAs increased sorafenib sensitivity to HCC cells (13,(38)(39)(40). In addition, inhibition of the activation of Akt may be a valid approach to treating human malignancies and overcoming the resistance of cancer cells to chemotherapy (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment outcomes are poor due to unfavorable pharmacokinetics, low tumor accumulation and high rates of sorafenib resistance in HCC patients (5). Evidence has shown that, some miRNAs increased sorafenib sensitivity to HCC cells (13,(38)(39)(40). In addition, inhibition of the activation of Akt may be a valid approach to treating human malignancies and overcoming the resistance of cancer cells to chemotherapy (41).…”
Section: Discussionmentioning
confidence: 99%
“…Among miR-486-5p target oncogenes that get activated following its downregulation in lung cancer include: CDK4, which promote cell cycle progression [3], ARHGAP5, which regulates cellular adhesion, motility, and polarity to promote cell migration and invasion [10], the growth promoting IGF signaling genes IGF1, IGF1R, and PIK3R1 [9], and the proto-oncogene serine/threonine kinase PIM-1 [8]. The tumor-suppressor role of miR-486-5p is also demonstrated in other cancers where it targets PIM-1 in breast cancer [43], SNAI1 in prostate cancer [44], and CLDN10, CITRON, and PIK3R1 in HCC [45,46] [45]. Although downregulation of this important tumor-suppressor miR in various cancer types is well-known, the mechanism of repression had not been delineated.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of the NAD+-dependent histone deacetylases, Sirtuin 1, is detected in HCCs with a higher tumor grade and is associated with poor survival as well as resistance to sorafenib [53]. Finally, expression of miRs that are considered to have tumor suppressor functions, such as miR-425-3p and miR-486, may also predict the effect of sorafenib [54,55]. Given the fact that a single miR targets multiple kinds of mRNA, constitutive activation of multiple molecules may act in concert to restore the sensitivity of HCC to sorafenib [56].…”
Section: Introductionmentioning
confidence: 99%